Romper a incabível prisão...: o processo de mudança de posição discursiva de sujeito-gago para sujeito-fluente. - Silva, Claudemir dos Santos (2021)
In the literature of stuttering studies, on the one hand, there are treaties that focus on biological, neurological and genetic aspects, more specifically, on the symptom of each patient's body, its anatomy and physiology, determining it as pathology without cure. On the other hand, there are postulations that focus on the subjects in their breadth, always considering your language. In view of this, the present thesis proposes the study of stuttering under the discursive perspective, because the subject, the language, as well as the ideology, the history and the senses must be thought in movement. Because in the discursive functioning, composed by the imaginary formations, linked to the production conditions, there is the establishment of ideological formations (FI), comprising interconnected discursive formations (FD). In this sense, we infer that stuttering is related to the discursive space, where the imaginary formations, united to the CP, with the performance of biopsychosocial factors, constitute the FD of subjects who stutter and the discursive position of subjects who stutter, produced considering the relation of forces, senses and anticipation and, as effects, we have the materialization of pauses, blocks, hesitations and/or prolongations. From this paradigm, as a general objective, we were able to analyze the process of changing the discursive position of the subject-stutterer to the fluent subject in Extension/Support Groups in Recife and Garanhuns. Our work was applied in extensions groups, support of Recife and Garanhuns, as basic attentions to education and health. Therefore, in reference of interiorization, we want the growth human resources and the activity of research in the State of Pernambuco. And in this situation we were helping, resignifying and giving force the process of changing of atitudes, showing for example, that the fluency is disfluent, in several discursive situation, in their respective context socio-historicalcultural. To do so, analyze or discuss the subjects having the Discourse Analysis (AD) as a theoretical and methodological framework, founded by Michel de Pêcheux, in France and discussed in Brazil, by authors such as Eni Orlandi and followers. In this way, the analysis of the corpus was carried out, considering the theoretical and methodological conceptions of AD. A research was of a qualitative nature, with participant observation, because it makes possible a relationship between the world and the subjects involved. It is linked to this, a longitudinal study, investigating a process of changes over time. From this, we proceeded with the discursive clippings, elected in view of linguistic-discursive marks, of four participants of the Extension/Support Groups, two from GEAG/UNICAP and two from UPE/Campus Garanhuns. Thus, we carried out the set of four discursive sequences (discursive corpus). So, throughout the analysis, we perceive the counter-identification and disidentification in the subject-form (contestations and transformation) in the subjectstutterer's FD and his subject-stutterer's discursive position, assuming himself in the fluent subject-FD and, respectively, a new subject-stanking position fluent. In the end, we hope that the discursive bias, which includes the subject and language, will contribute to illuminate studies in relation to stuttering and its consequences in groups such as the Teaching, Research and Extension.